2018
DOI: 10.1021/acsomega.7b02085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxygen Functional Groups on Reduced Graphene Oxide-Based Sensors for Ammonia and Toluene Detection at Room Temperature

Abstract: The chemically reduced graphene oxide (rGO) was prepared by the reduction of graphene oxide by hydrazine hydrate. By varying the reduction time (10 min, 1 h, and 15 h), oxygen functional groups on rGO were tremendously controlled and they were named RG1, RG2, and RG3, respectively. Here, we investigate the impact of oxygen functional groups on the detection of ammonia and toluene at room temperature. Their effect on sensing mechanism was analyzed by first-principles calculation-based density functional theory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 29 publications
(57 reference statements)
1
36
0
Order By: Relevance
“…The reason for this may be the structural dominance of graphene sheets over the disordered areas, which causes lowering of the intensity of D-band. 4245 For GO batch prepared using Marcano’s approach, the I D / I G ratio was determined as 1.18, which is lower compared to the I D / I G ratio for the GO (6 h) batch.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this may be the structural dominance of graphene sheets over the disordered areas, which causes lowering of the intensity of D-band. 4245 For GO batch prepared using Marcano’s approach, the I D / I G ratio was determined as 1.18, which is lower compared to the I D / I G ratio for the GO (6 h) batch.…”
Section: Resultsmentioning
confidence: 99%
“…Defect sites on graphene and graphene oxide act as suitable adsorption sites for various analytes, and it was reported that an increase in the I D /I G ratio generally results in improved gas sensing ability for graphene-based sensors. [20,49,50] The interplanar distance of the stacked GO sheets was determined by X-ray diffraction (XRD) as shown in Figure 4b. The 1.5 h GO has a slightly larger interplanar distance of 0.887 nm compared to 0.845 nm of the 1 h GO.…”
Section: Resultsmentioning
confidence: 99%
“…(28) The advantage of rGO over monolayer defect-free graphene is the presence of dangling oxygen functional groups on the graphene surface and edges. (65) Both theoretical and experimental results revealed that tuning of the oxygen functional groups on rGO plays a vital role in the detection of several organic compounds. Experimentally, oxygen functional groups can be tuned by adjusting the reduction time, the type of reducing agent, and the environment of reduction.…”
Section: Chemical Oxidation-reduction Methods For Graphitementioning
confidence: 99%
“…As reported by Minitha et al, the concentration of oxygen functional groups of rGO can be controlled by the aging time during the reduction process with hydrazine hydrate. (65) A higher concentration of oxygen functional groups yields a higher sensing response but poor recovery of the sensor. The sensor has difficulty in recovering its initial state since there are now more anchored functional groups in the graphene sheet, thus the recovery treatment should be several times higher.…”
Section: Detection Of Common Organic Vaporsmentioning
confidence: 99%